A novel pyroptosis-related indicator of immune infiltration features and prognosis in breast cancer - Wang, Cheng; Zhang, Liyong; Ren, Lin; Zhang, Guozhi; Wan, Andi; Xiong, Siyi; Tian, Hao; Peng, Zaihui; Zhao, Tingting; Gao, Pingping; Sun, Na; Zhang, Yi; et al. (Frontiers in Oncology, 2022)
Breast cancer is the most common malignancy in women and accumulating evidence elucidates the dual role of cell pyroptosis in tumor development. However, little is known about the relationship between cell pyroptosis and breast cancer and its prognostic value. We aimed to construct a prognostic model using cell pyroptosis-related genes to provide innovative insights into the prognosis and treatment of breast cancer. We screened candidate genes for pyroptosis using public databases and finally identify 10 cell pyroptosis signature genes by the random forest method. Finally, the nomogram for predicting one- , three-and five-year survival probabilities was constructed. Similar differences in the proportion of immune cell distributions were found between survival periods in different breast cancer datasets. The 10 key pyroptosis factors correlated significantly with Her2, stage and survival of breast cancer. The risk scores correlated positively with the infiltration features of B cells naive, CD8+ T cells, and mast cells, while they correlated negatively with those of macrophages M0 and DCs. In conclusion, our findings suggested that cell pyroptosis was closely associated with breast cancer, and risk scores generated from 10 cell pyroptosis-related genes assessed according to various clinical features may provide an important basis for future studies.